Psychosocial characteristics of patients evaluated for kidney, liver, or heart transplantation - Gronewold, Nadine; Schunn, Fabian; Ihrig, Andreas; Mayer, Gwendolyn; Wohnsland, Sascha; Wagenlechner, Petra; Leuschner, Maren; Kreußer, Michael; Sommerer, Claudia; Rupp, Christian; Friederich, Hans-Christoph; Schultz, Jobst-Hendrik; et al. (Psychosomatic medicine, 2023)
Objective: Psychosocial parameters play a pivotal role in organ recipient evaluation before wait-listing for transplantation because of their impact on organ and patient outcome. Patients in need of heart (HTx), liver (LTx), or kidney transplantation (KTx) face distinct physical and psychological challenges. This study compares the psychosocial characteristics and preferences for additional therapy for patients undergoing assessment for these three types of organ transplantation to optimize patient-tailored psychological, social, and other supportive interventions. Methods: We conducted a cross-sectional, observational study with 1110 potential transplantation candidates (LTx, n = 544; KTx, n = 330; HTx, n = 236), psychosocial status was determined for depressive symptoms (Patient Health Questionnaire Depression Scale), anxiety symptoms (seven-item Generalized Anxiety Disorder Screener), health-related quality of life (36-Item Short Form Health Survey), perceived social support (Perceived Social Support Questionnaire), sense of coherence (SoC; short form of the Sense of Coherence Scale), self-efficacy (General Self-Efficacy Short Scale), and body image (German Body Image Questionnaire-20). Preferences for additional supportive therapy were assessed dichotomously. Data were analyzed using multivariate analysis of covariance and χ2 tests. Results: Patient groups differed significantly regarding depression (F(2,1107) = 35.283, p < .001, partial η2 = 0.01), anxiety (F(2,1107) = 15.027, p < .001, partial η2 = 0.03), health-related quality of life (physical: F(2,1107) = 96.772, p < .001, partial η2 = 0.15; mental: F(2,1107) = 11.442, p < .001, partial η2 = 0.02), perceived social support (F(2,1107) = 20.813, p < .001, partial η2 = 0.04), SoC (F(2,1107) = 12.920, p < .001, partial η2 = 0.02), self-efficacy (F(2,1107) = 17.308, p < .001, partial η2 = 0.03), and body image (rejecting body evaluation: F(2,1107) = 5.006, p = .007, partial η2 = 0.01; vital body dynamics: F(2,1107) = 40.216, p < .001, partial η2 = 0.07). Patients evaluated for HTx showed the highest psychosocial impairment and the highest inclination regarding additional supportive therapy. Conclusions: Patients evaluated for HTx, LTx, and KTx have distinct psychosocial characteristics and treatment preferences. HTx patients display the highest psychosocial impairment. We suggest psychocardiological treatment structures for optimal outcome.
Gesehen am 10.05.2023